Economic Load Dispatch for Multi-Generator Systems with Units Having Nonlinear and Discontinuous Cost Curves Using Gravity Search Algorithm - Tunir Dey (Institute of Advanced Engineering and Science, 2014)
Economic Load Dispatch aims at distributing the load demand between various generation stations in a system such that the total cost of generation is minimum. This is of vital importance since it not only reduces the operation cost of the generation utility but also helps in conserving fast dwindling energy resources. Modern day power systems are large interconnected systems with a large number of generator units each having its own cost curve. Ideally the cost function of a unit is a quadratic function of the power generated by the unit and the cost curve obtained is a smooth parabola. But in practice cost curves deviate from the idealised one due the several reasons such as valve point effect, multi fuel operation, existence of forbidden zones etc. and as such may not be continuous or analytic. Also for a large interconnected system it becomes essential to consider the effect of transmission losses. Conventional numerical method based approaches work well with systems without losses but for large systems with losses obtaining convergence becomes difficult as the number of iterations required as well as the computational time are very high. These methods fail entirely if non ideal cost curves are considered. Hence soft computing based methods become essential. Here Gravity Search Algorithm(GSA) has been used to for finding economic load scheduling in a multi generator system, given a certain load demand, and taking into consideration the effects of practical constraints on the idealised load curve. The algorithms for finding the economic scheduling has been written in Matlab and has provided satisfactory results based on the given tolerance values. Also the traditional and soft computing based approaches have been compared to demonstrate the advantages of one over the other.